Students’ Perceptions of Using Traditional and Digital English Textbooks to Improve Students' Learning Interest - Ahmad Samat; Geminastiti Sakkir; Hasriani G (ITEKES Permata Ilmu Maros, 2026)
The purpose of this research is to analyze students’ perceptions of using traditional and digital English textbooks in improving learning interest. This study employed a quantitative method with subjects were 29 students of class XII.1 at SMAN 9 Tana Toraja, selected through cluster random sampling. Data was collected through a perception questionnaire. The results showed that students had positive perceptions of both types of textbooks. The use of traditional textbooks obtained a mean score of 44.38 with a standard deviation of 4.896, where 4 students (14%) were categorized as having very high perception and 25 students (86%) as high. Meanwhile, the use of digital textbooks obtained a mean score of 48.17 with a standard deviation of 5.795, with 15 students (52%) categorized as very high and 14 students (48%) as high interest. Therefore, it can be concluded that the use of textbooks, whether traditional or digital, contributes positively to students’ perceptions and learning interest.